An Interdisciplinary Approach for Rehabilitating a Patient with Amelogenesis Imperfecta: A Case Report - Niloufar Khodaeian; Mahmoud Sabouhi; Ebrahim Ataei (Hindawi Limited, 2012)
Amelogenesis imperfecta (AI) has been defined as a group of hereditary enamel defects. It can be characterized by enamel hypoplasia, hypomaturation, or hypocalcification of the teeth. AI may be associated with some other dental and skeletal developmental defects. Restoration for patients with this condition should be oriented toward the functional and esthetic rehabilitation. This clinical report describes the oral rehabilitation of a young patient diagnosed with the hypoplastic type of AI in posterior teeth and hypomatured type of AI in anterior teeth.